Britten et l’art de la parabole - Gilles Couderc (Revue LISA, 2004)
Between 1960 and 1971, Benjamin Britten seems to abandon large-scale opera in favour of more intimate pieces with a particularly obvious Christian message, his three "parables for church performances," which revisit medieval miracle plays through a specific musical language and stagecraft. Although quite original in Britten’s output, the parables hark back to older pieces also on religious subjects, composed between his operas. With hindsight it seems that Britten’s work as a whole springs from the concept of "parable-art." The aim of this paper is first to examine how Britten came to embrace as his own this concept inherited from his friends the poet W. H. Auden, the British documentary filmmaker John Grierson and the ideals of the American New Deal to become a "musician for an occasion," a composer whose mission is to educate his audience. It then proposes to look at the way parable-art is implemented in his operas. Through the adoption of the model of tragedy and oratorio with Britten’s own tragic heroes and tragic imagery, through the rhetoric of musical devices and forms and through social criticism and his indictment of Bible-thumping and dogmatic intellectuals, Britten the educator strives at raising the consciousness of his audience so as to better spread his humanistic message.